Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
-2x + 7y = 10 ⇒ -2x + 7y = 10
x - 3y = -3 ⇒ -2x + 6y = 6
y = 4
-2x + 7(4) = 10
-2x + 28 = 10
-28 -28
-2x = -18
-2 -2
x = 9
(x, y) = (9, 4)
x - 3y = -3 ⇒ -2x + 6y = 6
y = 4
-2x + 7(4) = 10
-2x + 28 = 10
-28 -28
-2x = -18
-2 -2
x = 9
(x, y) = (9, 4)
so
use elimintation
multily second equation by 2
2x-6y=-6
add to first equation
2x-2x+7y-6y=10-6
y=4
subsitute
x-3(4)=-3
x-12=-3
add 12 to both sdies
x=9
x=9
y=4
use elimintation
multily second equation by 2
2x-6y=-6
add to first equation
2x-2x+7y-6y=10-6
y=4
subsitute
x-3(4)=-3
x-12=-3
add 12 to both sdies
x=9
x=9
y=4
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.